Double‐targeted and double‐enhanced suicide gene therapy mediated by generation 5 polyamidoamine dendrimers for prostate cancer. Issue 3 (7th December 2011) - Chen, Yue; Wang, Gang; Kong, Deling; Zhang, Zhihong; Yang, Kuo; Liu, Ranlu; Zhao, Weiming; Xu, Yong
Abstract Herpes simplex virus (HSV)‐thymidine kinase (TK)/ganciclovir (GCV) system is one of the most widely used and efficient suicide gene therapy for prostate cancer, but the lack of favorable gene vector and target limits its application. In this study, we established a novel system using nonviral gene vector G5‐PAMAM‐D to express HSV‐TK and connexin43 (Cx43) gene driven by prostate‐specific membrane antigen (PSMA) promoter, and evaluated the anti‐tumor effect of this system. G5‐PAMAM‐D delivered PSMAe/p‐TK‐Cx43 showed expression of TK and Cx43 only in LNCaP cells, but not in PC‐3 and other cells. The transfection efficiency of this system was comparable to lipofectamine 2000 by propidium iodide staining assay. With gemcitabine, folate‐G5‐PAMAM‐D delivered PSMAe/p‐TK‐Cx43 (folate‐G5‐PAMAM‐D/PSMAe/p‐TK‐Cx43) significantly decreased prostate cancer LNCaP cell proliferation and promoted apoptosis in vitro. With gemcitabine, the systemic deliver of folate‐G5‐PAMAM‐D/PSMAe/p‐TK‐Cx43 significantly inhibited tumor growth in the LNCaP xenograft animal model. Our study demonstrates that this double‐targeted and double‐enhanced system is effective in inducing cell growth inhibition and apoptosis in vitro and suppressing tumor growth in vivo. In conclusion, Cx43 and gemcitabine combined with HSV‐TK/GCV gene therapy using nonviral vector G5‐PAMAM‐D hold great potential as a novel approach for the gene therapy of prostate cancer. © 2011 Wiley Periodicals, Inc.